#OnYGo - Blattner, Géraldine; Dalola, Amanda; Roulon, Stéphanie (Open textbook library., 2024)
#OnYGo is an innovative first-year French language e-textbook, designed as Open Educational Resource (OER), for learning beginning French (equivalent to one year at an American university). It is inspired by a remix of task-based, multiliteracies and communicative approaches, which provides students with opportunities to engage with French language and culture in a variety of contexts and situations, across a range of modalities. Through a wide range of activities, students develop and practice their language skills, and reflect on their cross-cultural knowledge and positionality in their understanding of the vast francophone landscape. #OnYGo is a first-year textbook that takes a DEI-forward approach to the depiction of people, contexts, and concepts. It views language learners, instructors and a wide range of individuals interacting in French as belonging to a large multilingual and francophone community. It recognizes multilingualism and multiculturalism in all its forms, and showcases French speakers with a variety of backgrounds and relationships to the French language. The cultural and pedagogical materials in this collection have been selected for their authenticity and diverse representation of French speakers on the five continents, and are thus purposely inclusive of gender, sexual orientation, race, and ethnicity.